PENGELOLAAN PEMBELAJARAN MELALUI PENERAPAN STRATEGI PEMBELAJARAN MULTI KECERDASAN PADA SISWA KELAS VII/A SMPN I PANGKALAN KERINCI - Fakhruddin Z; Zuhdi Ma’ruf; Yosie Kusmayenti (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2007)
The purpose of this research was to described ability in instructional manage physics class workand energy topic. With instructional strategic multiple intelligence applied on SMPN Pangkalan Kerinci onVII A classes students. Subject this research 40 students and data find out with filled observer sheets teachingand learning activity and classroom situation. From this research find mean 3,26 to manage of content ongood category, mean 3,28 instructional manage on good category and manage of student mean 3,13 withgood category.Key words: instructional manage, multiple intelligence